Implikasi Keluarga Terhadap Pendidikan Perspektif Qur’ani - M.Pd., Mudrikah (LP2M Sekolah Tinggi Islam Blambangan Banyuwangi, 2019)
Abstract: Education is a conscious and planned effort to create an atmosphere, learning process, and learning process so that students actively develop their potential to have religious spiritual strength, self-control, intelligence, noble character, and skills, which are needed by themselves, the nation and state. The National Education Objective is